2011
DOI: 10.3892/or.2011.1301
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of SIRT1 in hepatocellular carcinoma

Abstract: Abstract. silent mating type information regulation 2 homolog 1 (sIrt1) is a multifaceted, nicotinamide adenine dinucleotide-dependent protein deacetylase with involvement in a wide variety of cellular processes ranging from cancer to aging. expression of sIrt1 was evaluated in 90 cases of hepatocellular carcinoma (HCC) and five HCC cell lines. The relationship between the mutation status of p53 and expression of sIrt1 was also investigated in 10 fresh HCC tissues. synthetic small interfering rNA was used to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…It is already known that SIRT1 protein cooperates with DNMTs to repress transcription [33] and relevant chemotherapeutic drugs have already been tested in combination with DNMT inhibitors, HDAC inhibitors, and sirtuin inhibitors [32]. Moreover, SIRT1-silencing sensitized HCC cells to doxorubicin treatment [22]. A signaling cross talk between SIRT1 and STAT3 has been shown in the liver; STAT3 phosphorylation and function were found to be regulated by the nutritional status in mice, through SIRT1-mediated deacetylation of key STAT3 lysine residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that SIRT1 protein cooperates with DNMTs to repress transcription [33] and relevant chemotherapeutic drugs have already been tested in combination with DNMT inhibitors, HDAC inhibitors, and sirtuin inhibitors [32]. Moreover, SIRT1-silencing sensitized HCC cells to doxorubicin treatment [22]. A signaling cross talk between SIRT1 and STAT3 has been shown in the liver; STAT3 phosphorylation and function were found to be regulated by the nutritional status in mice, through SIRT1-mediated deacetylation of key STAT3 lysine residues.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have suggested a function of SIRT1 in HCC development [13,21,22]. In order to examine whether SIRT1 has a role in the modulation of DNMT1 and 3b expression induced by HCV core protein, we incubated Huh-7 cells expressing HCV core 1b with a SIRT1 inhibitor, sirtinol, to evaluate DNMTs expression.…”
Section: Dnmt1 and 3b Expression In Hcv Core Expressing Cells Upon Simentioning
confidence: 99%
“…SIRT1 is expressed in human HCC carcinoma tissues at a higher level than in adjacent nontumor liver tissues [43]. Furthermore, it was reported that patients with SIRT1-positive HCC have a lower 10-year survival rate than those with SIRT1-negative HCC [42, 44]. The downstream targets of SIRT1 include p53 [45, 46], telomerase [43], YAP (Yes-associated protein) [47], and PTEN/PI3K/Akt [48, 49] signaling, all of which can promote HCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, its expression status in melanoma is poorly defined and in need of further investigation. In cancers which overexpress SIRT1, inhibition through small molecule inhibitors or genetic knockdown leads to an induction of cell cycle arrest and/or apoptosis [9–14]. In breast cancer and chronic myeloid leukemia, this effect was shown to be accompanied by increased acetylation of the tumor suppressor p53 [11, 12].…”
Section: Introductionmentioning
confidence: 99%